Pengaruh Model Pembelajaran Creative Problem Solving Terhadap Keterampilan Pemecahan Masalah dan Hasil Belajar Kognitif Siswa - Mbembok, Rosmianti Lestari; Fatmawati, Any; Adawiyah, Siti Rabiatul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2017)
This research with the aim to know the influence of the use of Creative Problem solving learning model on problem solving skills and cognitive learning outcomes of grade X SMA Islam Al-Ma’arif Pandan Indah Lesson 2016/2017. Population in this research is all student of class X SMA Islam Al-Ma’arif Pandan Indah Lesson Year 2016/2017 with amount of population counted 36 person which existed in class XA and XB. Furthermore, sampling technique used is a saturated sampling technique that is sampling technique when all members of the population used as a sample. Where class XA as experiment class and XB as control class. The type of research used in this study is quasi experiment with observation and test data collection techniques. The results showed that problem solving skills in the first experimental classroom obtained an average percentage of 66% included in the good category, while in the second meeting obtained an average percentage of 79% included in the category of very good. The students’ cognitive learning outcomes in the experimental class were 70.4 and the control class was 66.2. The result of hypothesis test with t test at 5% significant level shows that tcount> ttable (2,675> 2,042), meaning H0 is rejected. So it can be concluded that there is influence Creative Problem Solving learning model to problem solving skills and student cognitive learning outcomes.